2011
DOI: 10.1124/jpet.111.184275
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Effects of Imperatorin on Allergic Rhinitis: Imperatorin Inhibits Caspase-1 Activity In Vivo and In Vitro

Abstract: Because imperatorin (IPT), the furanocoumarins exhibits antiinflammatory activity, we reasoned that IPT might modulate the allergic rhinitis (AR). The aim of this study was to analyze the regulation of AR by IPT. Here, we show the effect and mechanism of IPT in an ovalbumin (OVA)-induced AR model. The number of rubs after the OVA challenge in the OVA-sensitized mice was significantly higher than that in the OVA-unsensitized mice. The increased number of rubs was inhibited by the oral administration of IPT. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…In the present study, we observed large number of hemosiderin leyden macrophages as well as thick fibrous capsule in the section of spleen and corresponding enlargement of spleen in AR control mice. Our observations are in line with previous reports of splenic enlargement and cellular infiltration (neutrophils, eosinophils and mast cells) caused by OVA sensitization in rats (Oh et al , ). TAPP‐CZ treatment was found to significantly prevent OVA‐induced splenic enlargement and cellular infiltration in present study indicating beneficial effects against immune inflammation such as AR.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observed large number of hemosiderin leyden macrophages as well as thick fibrous capsule in the section of spleen and corresponding enlargement of spleen in AR control mice. Our observations are in line with previous reports of splenic enlargement and cellular infiltration (neutrophils, eosinophils and mast cells) caused by OVA sensitization in rats (Oh et al , ). TAPP‐CZ treatment was found to significantly prevent OVA‐induced splenic enlargement and cellular infiltration in present study indicating beneficial effects against immune inflammation such as AR.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Gami‐hyunggyeyeongyotang, which is a polyherbal medicine derived from an oriental prescription traditionally used for the treatment of allergic diseases, can attenuate allergic inflammation in AR by suppressing IL‐1β and caspase‐1 expression via the inflammatory pathway in human mast cells . Several other research studies have revealed that the levels of IL‐1β and caspase‐1 in the serum or nasal mucosa tissue were increased in the OVA‐induced AR mice compared with those in the control mice and that the administration of anti‐allergic drugs inhibited IL‐1β and caspase‐1 expression and attenuated the allergic symptoms …”
Section: Role Of Il‐1β and Il‐18 In Armentioning
confidence: 99%
“…The development of AR is a rather complicated process involving sensitization by allergens, expression of antigen specific IgE, degranulation of mast cells and release of inflammatory mediators, such as histamine, tryptase, prostaglandins and leukotrienes, and intramucosal inflammatory cell infiltrations. TDI is a highly active chemical agent that can induce the activation of the mast cells, leading to a hypersensitive reaction in the nasal cavity of guinea pigs [ 24 ]. When treated with BLG at different doses, AR symptoms of the experimental animals were obviously alleviated [ 25 ].…”
Section: Discussionmentioning
confidence: 99%